Consumer loan as one of the mechanisms of fiscal policy to achieve social justice - Haddad, Rokia (Milev Journal of Research and Studies, 2022)
The fiscal policy is one of the most important tools for the management of the national economy, And by which the state achieve the desired economic goals. Consumer Loan decision came as one of the mechanisms of fiscal policy, Which aims Algeria through which to achieve social justice in light of the financial and economic crisis, because of the collapse of the oil price and the devaluation of the Algerian dinar, which in turn reflected on the purchasing power and standard of living of the Algerian citizen.